In vitro differentiation of neural stem cells derived from human olfactory bulb into dopaminergic‐like neurons. (1st March 2017) - Alizadeh, Rafieh; Hassanzadeh, Gholamreza; Joghataei, Mohammad Taghi; Soleimani, Mansoureh; Moradi, Fatemeh; Mohammadpour, Shahram; Ghorbani, Jahangir; Safavi, Ali; Sarbishegi, Maryam; Pirhajati Mahabadi, Vahid; Alizadeh, Leila; Hadjighassem, Mahmoudreza
Abstract: This study describes a new accessible source of neuronal stem cells that can be used in Parkinson's disease cell transplant. The human olfactory bulb contains neural stem cells (NSCs) that are responsible for neurogenesis in the brain and the replacement of damaged cellular components throughout life. NSCs are capable of differentiating into neuronal and glial cells. We isolated NSCs from the olfactory bulb of brain‐death donors and differentiated them into dopaminergic neurons. The olfactory bulb tissues obtained were cultured in Dulbecco's modified Eagle's medium/nutrient mixture F12, B27 supplemented with basic fibroblast growth factor, epidermal growth factor and leukemia inhibitory factor. The NSCs and proliferation markers were assessed. The multipotentiality of olfactory bulb NSCs was demonstrated by their capacity to differentiate into neurons, oligodendrocytes and astrocytes. To generate dopaminergic neurons, olfactory bulb NSCs were differentiated in neurobasal medium, supplemented with B27, and treated with sonic hedgehog, fibroblast growth factor 8 and glial cell‐derived neurotrophic factor from the 7th to the 21st day, followed by detection of dopaminergic neuronal markers including tyrosine hydroxylase and aromaticl ‐amino acid decarboxylase. The cells were expanded, established in continuous cell lines and differentiated into the two classical neuronal phenotypes. The percentage of co‐positive cells (microtubule‐associated protein 2 and tyrosine hydroxylase; aromatic l‐amino acid decarboxylase and tyrosine hydroxylase) in the treated cells was significantly higher than in the untreated cells. These results illustrate the existence of multipotent NSCs in the adult human olfactory bulb that are capable of differentiating toward putative dopaminergic neurons in the presence of trophic factors. Taken together, our data encourage further investigations of the possible use of olfactory bulb NSCs as a promising cell‐based therapeutic strategy for Parkinson's disease. Abstract : The human olfactory bulb neural stem cells (OB‐NSCs) could be isolated. OB‐NSCs are capable to differentiate to dopaminergic‐like cells as a promising tool in Parkinson disease therapy.